(untitled) (Global Journal of Human-Social Science, 2015)
Land is the most critical factor of production for a myriad of economic activities for human settlement worldwide although it is in limited supply. It is therefore, essential that its allocation across different economic activities and uses should be based on sound theoretical premises, combined with the ground realities of multiple objectives -a few of which regularly exceed the narrowly defined goals of economic growth per se. For traditional communities, ’access to lands is directly associated with civilization paradigms and cultural ethos, which rather decide their ’economics’, and not one other way round that could be true for modern, technocentric civilizations. Most mainstream discourses of history have, however, tried to find the crisis in the ’absence of state interventions and a dig into the social history points to deeper roots of the crisis, which rather intensified after the entry of the ’welfare’ state. In a predominantly, agrarian economy such as for example in India and Odisha, the entitlement to livelihood and access to the factors of production, especially land and forests, are essential objectives that require to ascertain allocation of land across different uses and users.